Timely directional data delivery to multiple destinations through relay population control in vehicular ad hoc network. (May 2020) - Lee, Seona; Lee, Sang-Ho; Lee, HyungJune
In this article, we consider a directional data forwarding problem to multiple destinations under distinct deadline constraints in vehicular ad hoc networks. We present a simple yet effective data forwarding algorithm based on only vehicle-to-vehicle communications in infrastructure-less and map-less environments. Our algorithm consists of two phases: relay selection and proliferation . We design a relay selection algorithm that encourages a shared ride for data delivery toward a certain common intermediate point from time to time for forwarding efficiency. It chooses a strong next relay candidate among nearby connected vehicles by considering their current position, velocity, and also the current progress toward the destination. In case that one of the progress lagging indicators becomes signaled, the number of vehicle relays increases under control depending on the degree of deterioration during a packet replication procedure called proliferation . Embedding two essential parts in designing a timely data forwarding scheme validates its accurate on-time data delivery performance and forwarding efficiency in network overhead based on real-world data-driven experiments.